Men’s and women’s sustenance activities in court records from Sunne hundred in the province of Jämtland, Sweden, 1840–1859 - Kardell, Örjan; Jansson, Karin Hassan (Uppsala University, 2026)
The dataset consists of extracts from court records from Sunne tingslag in Jämtland from 1840 to 1859. The extracts contain written descriptions of sustenance activities performed by one or more individuals. These source texts have been transcribed and analyzed within the project Gender and Work (phase 3) at Uppsala University and have been selected with the aim of clarifying the context in which individuals and livelihood activities occur.

The dataset contains (a) a list of activities described in the court records, with variables specifying who performed the activity, when and where it was performed, and under what circumstances, and (b) transcriptions of the cases in the court records from which the activities are extracted.

Source texts and source-based variables have been registered faithfully to the letter primarily by Örjan Kardell and, in a few cases, by Karin Hassan Jansson, both researchers in the project Gender and Work. Quality control has been carried out by Jonas Lindström. The material is searchable in the database GaW: https://www.uu.se/forskning/gender-and-work

Datasetet består av utdrag ur domböcker från Sunne tingslag i Jämtland från vårtinget år 1840 till och med hösttinget år 1859, samt urtima ting och syner år 1840–1859. Utdragen innehåller skriftliga beskrivningar av försörjningsaktiviteter som utförts av en eller flera individer. Dessa källtexter har transkriberats och analyserats inom projektet Genus och arbete (fas 3) vid Uppsala universitet samt valts ut i syfte att klargöra sammanhanget där individ och försörjningsaktivitet förekommer.

Datasetet innehåller (a) en lista över aktiviteter som beskrivs i domstolsregistren, med variabler som specificerar vem som utförde aktiviteten, när och var den utfördes, och under vilka förhållanden, och (b) transkriptioner i de fall i domstolsregistren från vilka aktiviteterna är extraherade.

Källtexter och källtrogna variabler har registrerats bokstavstroget av i första hand Örjan Kardell och i ett fåtal fall från vårtinget år 1840 av Karin Hassan Jansson, båda forskare inom projektet Gender and Work. Kvalitetskontroll är utförd av Jonas Lindström. Materialet är sökbart i databasen GaW: https://www.uu.se/forskning/gender-and-work
Uppgifter om mäns och kvinnors försörjningsaktiviteter i domböcker från Sunne tingslags häradsrätt, Jämtland perioden 1840–1859
Sunne (Jämtland), häradstingets protokoll 1840–1859
Keywords: LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; HISTORY AND ASSOCIATED STUDIES; HISTORIA OCH NÄRBESLÄKTADE ÄMNEN; HISTORY; HISTORIA; social gender; genus; gender research; genusforskning; history (discipline); Mode of collection; Insamlingssätt; Sampling procedure; Urvalsprocess; Time unit; Tidsenhet; Geographic unit; Geografisk enhet; Data source type; Källtyp; Gender Studies; Genusstudier; History; Historia